Mengatasi Dikotomi Pendidikan Islam di Indonesia dengan Prinsip Integral dan Terpadu - Fajri, Encep Muhammad; Al Hamdani, Djaswidi; Rizal, Soni Samsu (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Education is currently experiencing a decline due to the frequent imbalance between general education and religious education, especially Islam, resulting in the emergence of an educational dichotomy. This research was created with the aim of studying and understanding the dichotomy problems that occur in Indonesia. The type of research used is qualitative using the literature review method. The data sources used are secondary data sources which refer to books and articles. The data analysis technique is by examining all the data collected, then abstracting the data and the next stage is checking the validity of the data and interpreting the data. The results of the research explain that the educational dichotomy is a problem that is considered quite complicated because the educational dichotomy that is currently occurring in Indonesia has spread to various educational sectors. The historical roots of this dichotomy begin with the entry of Dutch colonialists into Indonesia and changing the existing education system. Based on these problems, a solution is needed to overcome the educational dichotomy. Integral and integrated principles are the right solution to overcome these problems, which can provide harmony between religious knowledge and general science.